Electrochemistry and Electrocatalysis of Hemoglobin Based on Graphene Quantum Dots Modified Electrode - Li, Xiaoyan; Xie, Hui; Luo, Guiling; Niu, Yanyan; Li, Xiaobao; Xi, Yaru; Xiong, Yi; Chen, Yong; Sun, Wei (Current Analytical Chemistry, 2020)
Background: Graphene quantum dots (GQD) is a new member of carbon nanomaterial that has attracted increasing attention owing to its better chemical inertness, low cytotoxicity, large specific surface area, cheap cost, suitable conductivity and excellent biocompatibility. Methods: Electrochemical behaviors of this modified electrode were studied by cyclic voltammetry and electrochemical impedance spectroscopy. Electrochemical investigations of Nafion/Hb/GQD/ CILE were carried out with electrochemical parameters calculated. Results: In the phosphate buffer solution with a pH value of 5.0, good linear relationships between the catalytic reduction current and the concentration of substrate were got for TCA (6.0 100.0 mmol·L-1), NaNO2 (2.0 12.0 mmol·L-1) and H2O2 (6.0 30.0 mmol·L-1). The proposed method was applied to NaNO2 concentration detection in soak water from picked vegetables with satisfactory results. Conclusion: This Nafion/Hb/GQD/CILE had a good bioelectrocatalytic activity to different substrates such as trichloroacetic acid, NaNO2 and H2O2 reduction with the advantages including wide detection range, low detection limit and good stability. Therefore, the application of GQD in electrochemical sensor was extended in this paper.
Keywords: graphene quantum dots